Addressing the refugee problem in the early of 21st century by UNHCR - Aizat Khairi,; Mohd Ramlan Mohd Arshad,; Mohd Na’eim Ajis, (Penerbit Universiti Kebangsaan Malaysia, 2023)
UNHCR as an international UN agency that focuses on helping to deal with international refugee problems has faced bitter challenges as early as the 21st century. This is due to the financial problems faced by UNHCR and also the change in refugee trends as a result of internal conflicts in certain countries. UNHCR's main challenge during this era is to fend off the accusations of the international community in the refugee destination country's negative perception of this group. Thus, UNHCR's approach changes in line with international political currents by strengthening the element of responsibility to protect. This approach is to strengthen the protection of refugees in the country of destination and UNHCR also cooperates with the government in the country of destination in terms of finance, mobilization, registration and resettlement. This effort is seen as potentially helping to deal with the refugee problem collectively and continuously until this issue is successfully resolved comprehensively